UPAYA MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN DENGAN MEDIA KARTU HURUF PADA SISWA KELAS 1 SEMESTER II (GENAP) TAHUN 2022 MI. MA. SINDANGLAYA BOJONG - Nurbaeti, Siti; Kosasih, Kosasih; Hidayatullah, Agus (Staisman Press, 2022)
Education is the main key in the development of the nation, through education everyone can gain knowledge and knowledge to improve their quality. The implementation of education in schools, especially Elementary School Education (SD/MI) must pay attention to the diversity of students' abilities, both in thinking ability and skill ability. Therefore, through basic education students are equipped with basic skills such as reading. This study aims to determine the efficiency and effectiveness of letter card media in improving the early reading ability of first grade MI students. MA. Sindanglaya Bojong. The formulation of the problem in this study is 1) How are the efforts made by the teacher in increasing the difficulty of reading at the beginning of class 1 MI. MA. Sindanglaya Bojong?, 2) The factors that cause children to have difficulty in reading?. This research was conducted using the CAR Method, which is a form of action taken by a teacher in the classroom which aims to improve the quality of the learning process and student learning outcomes in the classroom. With research actions carried out in two cycles. Each cycle consists of planning, implementation, observation/observation, and reflection. The target of this research is the Class I MI students. MA. Sindanglaya Bojong totaling 22 people with a composition of 9 women and 13 men. The results showed that letter card media could improve students' initial reading skills. It can be seen from the increase in the initial reading ability in each cycle, during the pre-cycle it showed 31.81% results, then increased in the first cycle which was 54.45%, and increased in the second cycle to 86.36%.